Nurses' Knowledge And Practice In Gastrointestinal Endoscopy: Developing Nursing Guidelines (Journal of Namibian Studies : History Politics Culture, 2023)
Nurse health professionals play vital roles in the delivery of healthcare today, which include professionalism, leadership, caregiver, patient, and family advocacy, education, collaboration, accountability, and maintaining quality. Endoscopy nurses have a central role in the efficient running of the endoscopy service. Nurses have been increasingly involved in non-complex gastrointestinal endoscopy as changes in health systems have developed and expanded. The successes and effectiveness of the endoscopy unit need a collaborative team of nurses, doctors, and other health professionals, which perform work in a planned, organized, and systematic way at the endoscopy unit. Due to their close relationship with the patient, educators, and administrators and the growing amount of invasive procedures carrying potential harmful effects on the patient and socioeconomic consequences, in the event of complications and complaints, the roles and responsibilities of the nurse should be re-evaluated.